DECISION SUPPORT SISTEMS (DSS) DETERMINING DEPARTMENT USING NAIVE BAYESIAN ALGORITHM - NURLINDASARI TAMSIR (Journal of Information Technology and Its Utilization, 2018)
In practice the majors are often determined by the teacher with consideration of academic achievement and ignore the interests and talents of the students. Students who have high scores on the grades of report cards will be educated on IPA and low achievers will be led to IPS and Language. Problems faced by most schools because students who enter the majors are not in accordance with the skills, abilities, interests and talents of students that affect the quality and success of student learning. With the majors in accordance with the characteristics of personality, students will feel happy when learning so as to help prepare students to continue their studies and choose the world of work and help strengthen the achievements to be achieved in the future. The purpose of this study is to find out how the implementation of Decision Support Sistems (DSS) using the Naive Bayesian method in determining the department in accordance with the skills, abilities, interests and talents of students held in SMA Negeri 10 Makassar and SMA Islam Athirah Makassar. Technique of data retrieval is done by observation and direct interview. The instrument used is a validated questionnaire by 2 (two) validators to test the questionnaire validity. There are two types of data that are analyzed ie student value data and questionnaire data that generate interest and talent of students to determine the direction. It is expected that with this application it can be seen that the students go to the department has been in accordance with the potential of each student.